Novel Treatments in Lupus - Vukelic, Milena; Li, Yi; Kyttaris, Vasileios C. (Frontiers in Immunology, 2018)
The standard treatment options for systemic lupus erythematosus (SLE) are focused on non-specific immunosuppression. Over the past few years, scientific studies and ongoing clinical trials have shifted the paradigm with rapid advances in developing biologics and small molecules. A number of monoclonal antibodies and small molecule inhibitors have been developed to target specific pathways involved in SLE. Many of these novel therapeutic agents are already being tested in clinical trials and they may one day reshape the landscape of SLE treatment. Herein we review potential future therapeutic options for SLE.